Relation between the Dantu blood group variant and bacteremia in Kenyan children: a population-based case-control study - Kariuki, SN; Gilchrist, JJ; Uyoga, S; Macharia, A; Makale, J; Rayner, JC; Williams, TN (Oxford University Press, 2024)
Background: The Dantu blood group variant protects against Plasmodium falciparum infections, but its wider consequences have not been previously explored. Here, we investigate the impact of Dantu on susceptibility to bacteremia. Methods: We conducted a case-control study in children presenting with community-acquired bacteremia to Kilifi County Hospital in Kenya between 1998 and 2010. We used logistic regression to test for associations between the Dantu marker single-nucleotide polymorphism rs186873296 A > G and both all-cause and pathogen-specific bacteremia under an additive model. We used date of admission as a proxy measure of malaria transmission intensity, given known differences in malaria prevalence over the course of the study. Results: Dantu was associated with protection from all-cause bacteremia (OR, 0.81; P = .014), the association being greatest in homozygotes (OR, 0.30; P = .013). This protection was shared across the major bacterial pathogens but, notably, was only significant during the era of high malaria transmission pre-2003 (OR, 0.79; P = .023). Conclusions: Consistent with previous studies showing the indirect impact on bacteremia risk of other malaria-associated red cell variants, our study also shows that Dantu is protective against bacteremia via its effect on malaria risk. Dantu does not appear to be under balancing selection through an increased risk of bacterial infections.